2022
DOI: 10.1002/acr.24474
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Ancestral Diversity in Systemic Lupus Erythematosus Clinical Studies

Abstract: Non-White people are more likely to develop systemic lupus erythematosus (SLE) yet are underrepresented in SLE clinical trials. The efficacy and safety of drugs may be influenced by ancestry, and ancestrally diverse study populations are necessary to optimize treatments across the full spectrum of patients. However, barriers to entry into clinical trials are amplified in non-White populations. To address these issues, a conference was held in Bethesda, Maryland, from October 15-16, 2019, entitled "Increasing A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…26,27 A strength of this study is the high proportion of Black pregnant women with SLE, a group that is often under-represented in clinical research. 21,28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 A strength of this study is the high proportion of Black pregnant women with SLE, a group that is often under-represented in clinical research. 21,28…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A strength of this study is the high proportion of Black pregnant women with SLE, a group that is often under-represented in clinical research. 21,28 Few studies have evaluated racial disparities in pregnancy outcomes among women with SLE and LN. The LUMINA study, a multiethnic study of patients with SLE, revealed a 5-fold odd of adverse pregnancy outcomes in women with kidney involvement prior to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…To address the lack of adequate representation of racial minority groups in SLE research, a 2019 conference among patients with SLE, SLE physicians, clinical trialists, treatment developers from biotechnology, social scientists, patient advocacy groups and US government representatives explored solutions for increasing diversity in SLE research studies. 19 Best practices for clinicians and researchers were developed, which included reflecting on how personal and institutional culture lead to racial bias in research questions and study design, the need to avoid making assumptions about the ‘kind’ of patient who would participate in a trial, and increasing recruitment of under-represented minorities to the field of rheumatology. Experts in our study expressed several opportunities to address these issues, including having a diverse research staff, including outcomes that are important to patients and utility of funding for patient navigators ( box 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The principle of justice highlighted in the Belmont Report calls for equitable distribution of the benefits and risks of participating in research across the populations affected by a disease (8). While race is a social rather than biological construct, genetic polymorphisms that vary by ancestry can influence a drug's safety and efficacy (9,10). More balanced representation of racial and ethnic groups in clinical research is imperative to achieving health equity.
Through community–academic partnerships in Boston and Chicago, we developed a now freely accessible curriculum to promote better understanding of clinical trials, acknowledging the history of racism in medical research and barriers and facilitators of participation. We utilized a popular opinion leader (POL) model to recruit and train leaders from predominantly Black communities to disseminate information through their social networks and communities.
…”
Section: Introductionmentioning
confidence: 99%
“…The principle of justice highlighted in the Belmont Report calls for equitable distribution of the benefits and risks of participating in research across the populations affected by a disease ( 8 ). While race is a social rather than biological construct, genetic polymorphisms that vary by ancestry can influence a drug's safety and efficacy ( 9 , 10 ). More balanced representation of racial and ethnic groups in clinical research is imperative to achieving health equity.…”
Section: Introductionmentioning
confidence: 99%